2019
DOI: 10.1055/s-0039-1693125
|View full text |Cite
|
Sign up to set email alerts
|

New Technology of Thermoplastic Coating for Osmotic Pump Tablets: Study on in vitro Drug Release

Abstract: Aim The in vitro drug release profiles of metformin hydrochloride thermoplastic coated tablets and nifedipine thermoplastic coated tablets were studied. Methods By measuring the in vitro release profiles of the thermoplastic coated tablets of model drugs, the effects of membrane thickness, polyethylene glycol-1,500 (PEG1500) content, number of orifice, stirring speed, and release medium on the drug release were investigated, and the rule and mechanism of drug release were also analyzed by comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The in vitro drug-release profiles of M15-80 and N5-90 were studied according to "Determination of Release Profiles" described in the previous article "New Technology of Thermoplastic Coating for Osmotic Pump Tablets: Study on in vitro Drug Release." 3 The release data of M15-80 and N5-90 were fitted with drug-release models, such as zero-order, first-order, and the Higuchi square-root of time release equations by calculating the correlation coefficient r 2 , 4 respectively.…”
Section: Determination Of Release Profiles and Drug-release Models Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro drug-release profiles of M15-80 and N5-90 were studied according to "Determination of Release Profiles" described in the previous article "New Technology of Thermoplastic Coating for Osmotic Pump Tablets: Study on in vitro Drug Release." 3 The release data of M15-80 and N5-90 were fitted with drug-release models, such as zero-order, first-order, and the Higuchi square-root of time release equations by calculating the correlation coefficient r 2 , 4 respectively.…”
Section: Determination Of Release Profiles and Drug-release Models Ofmentioning
confidence: 99%
“…The preparation process of a new thermoplastic coating technology (HHL method), 1 the properties of the thermoplastic coating membrane, 2 and the in vitro release profiles of thermoplastic-coated tablets 3 have been published separately previously. In vitro release studies showed that thermoplastic-coated tablets possessed the same release mechanism (osmotic pressure drove the drug release) and the same release characteristics (zero-order release, unaf-fected by the release medium and stirring speed) and the same release rule (the release rate was inversely proportional to the membrane thickness but proportional to the porogen content) as the osmotic pump tablets (OPTs) prepared by the conventional spray coating, therefore displayed the same characteristics as OPTs.…”
Section: Introductionmentioning
confidence: 99%